Gender, Self-Esteem, Communication Parents/Teenagers and Behviour at Risk Early Pregnancies in Environment School: The Case of Côte d'ivoire (Common of Yopougon) - , Goubo Aka Rene; , Yao Kouakou Martial (Archives of Current Research International, 2022)
This study aims to analyze the relationship between gender, self-esteem, the communication parents/teenagers and the behaviours at risk of pregnancies early in environment school. She carries on a sample of six hundred four (604) teenage girls and we selected three one hundred and five eight (358) students- adolescent girls from the sixth to the final year in the municipality of Yopougon whose age varies from 10 to 19 years. Thus, we used as a sampling technique the proportional allocation of quotas. The sample is submitted to a questionnaire the results of which are analyzed using the method statistical who does not require than the quantification from data collected. The method qualitative at summer too used through content analysis more specifically indexing. Thus, the results of our investigation according to the chi of them of person calculated, we at permit of to confirm than gender has a significant effect on early pregnancy risk behaviors at the house of the teenage girls. Too, the variables intermediaries who are associated at the gender variable out of seven (7) three variables were confirmed, namely the context of the action, the goal of the action and the history of the action. Thereby, she come complete reflections on the links between gender, self-esteem, communication parents/teenagers and the behaviours at risk of pregnancies early in environment school.